2022
DOI: 10.3389/fphar.2022.857730
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and System Biology Approach to Reveal the Interaction Network and the Therapeutic Implications for Non-Small Cell Lung Cancer Patients With COVID-19

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the leading cause of coronavirus disease-2019 (COVID-19), is an emerging global health crisis. Lung cancer patients are at a higher risk of COVID-19 infection. With the increasing number of non-small-cell lung cancer (NSCLC) patients with COVID-19, there is an urgent need of efficacious drugs for the treatment of COVID-19/NSCLC.Methods: Based on a comprehensive bioinformatic and systemic biological analysis, this study investigated COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 213 publications
(202 reference statements)
0
3
0
Order By: Relevance
“…Several studies have previously highlighted the role of p53 in SARS-CoV-2 infection [ 34 , 35 ], pointing out p53 as a potential target for the development of antivirals [ 36 , 37 ]. In contrast, our data show that the increase in SARS-CoV-2 replication observed when the cells are stopped in G1 is p53-independent, making the use of p53 targeting antivirals ineffective in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously highlighted the role of p53 in SARS-CoV-2 infection [ 34 , 35 ], pointing out p53 as a potential target for the development of antivirals [ 36 , 37 ]. In contrast, our data show that the increase in SARS-CoV-2 replication observed when the cells are stopped in G1 is p53-independent, making the use of p53 targeting antivirals ineffective in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The study increased the pathophysiological understanding of COVID-19 and NSCLC. 111 Upon investigating the clinical management of NSCLC patients during the first wave of COVID-19, it was found that a considerably diminished diagnosis of lung cancer cases was being done. Telemedicine helped in patienthealthcare interactions and in administering concurrent therapeutic regimes for managing lung cancer patients with COVID.…”
Section: Lung Cancermentioning
confidence: 99%
“…The enrichment analysis revealed common signaling pathways between COVID‐19 and NSCLC. The study increased the pathophysiological understanding of COVID‐19 and NSCLC 111 . Upon investigating the clinical management of NSCLC patients during the first wave of COVID‐19, it was found that a considerably diminished diagnosis of lung cancer cases was being done.…”
Section: Unveiling the Lethal Convergence: Exploring The Intersection...mentioning
confidence: 99%